2018
DOI: 10.1080/2162402x.2018.1442999
|View full text |Cite
|
Sign up to set email alerts
|

TIME (Tumor Immunity in the MicroEnvironment) classification based on tumor CD274 (PD-L1) expression status and tumor-infiltrating lymphocytes in colorectal carcinomas

Abstract: Inhibitors targeting the (programmed cell death 1, PD-1) immune checkpoint pathway have revolutionized cancer treatment strategies. The TIME (Tumor Immunity in the MicroEnvironment) classification based on tumor ( ligand 1, PD-L1) expression and tumor-infiltrating lymphocytes (TIL) has been proposed to predict response to immunotherapy. It remains to be determined clinical, pathological, and molecular features of TIME subtypes of colorectal cancer. Using 812 colon and rectal carcinoma cases from the Nurses' He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 66 publications
3
43
1
Order By: Relevance
“…The inter‐patient and inter‐tissue variability of PD‐L1 by our IHC detection demonstrates that the expression of PD‐L1 may differ between different lung cancer cohorts, and may be influenced by various factors, including tumor types, genetic backgrounds, and inflammation. It was reported that TMIT stratification of colorectal cancer was associated with high levels of microsatellite instability and neoantigen load, supporting better response to ICI . However, the analysis was based on the TILs counting in both tumor and adjacent stroma together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter‐patient and inter‐tissue variability of PD‐L1 by our IHC detection demonstrates that the expression of PD‐L1 may differ between different lung cancer cohorts, and may be influenced by various factors, including tumor types, genetic backgrounds, and inflammation. It was reported that TMIT stratification of colorectal cancer was associated with high levels of microsatellite instability and neoantigen load, supporting better response to ICI . However, the analysis was based on the TILs counting in both tumor and adjacent stroma together.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that TMIT stratification of colorectal cancer was associated with high levels of microsatellite instability and neoantigen load, supporting better response to ICI. 29 However, the analysis .059…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy, as a tool for cancer management, has gained significant importance. Additionally, activation of immune system and subsequent immune reaction play an important role in tumor microenvironment in suppressing tumor development and progression [147] . The presence of TILS provides evidence that the host's immune system is attempting to eliminate the tumor, and this is an important favorable prognostic factor in CRC [148] , [149] .…”
Section: Discussionmentioning
confidence: 99%
“…3 The mismatch repair (MMR)/microsatellite instability (MSI) pathway significantly contributes to CRC development 12,13 and is associated with the immune microenvironment. 14,15 However, although the distinct features of MSI-high (MSI-H) tumors have been identified, 16 MSI status of the primary CRC versus its metastatic lesions has not been fully explored. Change in MSI status is important because studies have shown that only patients with deficient MMR (dMMR) or MSI-high tumors benefit from anti-PD-1 therapy.…”
Section: Introductionmentioning
confidence: 99%